Pulses for zero hunger and zero malnutrition - Singh, N. P.; Pratap, Aditya (Indian Farming, 2018)
Pulses are grown across a range of farming systems, agro-ecologies and socio-economic strata. Nutritional and health benefits of pulses are many and their major inclusion in predominantly vegetarian diets will lead the world towards zero hunger and zero malnutrition. Nevertheless, as also stated in Morocco declaration on ‘Pulses: solutions to food and nutrition security, agricultural sustainability and climate change adaptation’, their role in global health including the reduction of noncommunicable disease such as obesity, diabetes, heart and neurodegenerative diseases is understated. Community-level nutrition education programmes and trainings to broaden and diversify the use of pulses at household-level need attention. Simultaneously, commercial production of pulse-based complimentary foods and economic usage of pulses byproducts for preparation of fortified diets need impetus. Remarkable growth has been achieved in indigenous pulses production in India in recent years and measures for its sustenance, profitability and acceptability are required to be adopted. Rapid mixing and instant fixing’ approach needs to be adopted through speed breeding concept in pulses to for continual development of new, higher yielding, multiple pests- and disease resistant and climate resilient crop varieties that meet both farmer needs and consumer preferences. Adoption of improved varieties, timely availability of quality seed coupled with recommended package of practices can significantly enhance the productivity of small holder farmers in India. Enhanced pulse production creates a host of opportunities for local value added processing, stimulates domestic demands and provides off-farm employment and sources of income to rural poor. While pulses directly benefit the farm families by eradicating protein energy malnutrition, indirectly they contribute more to the socioeconomic upliftment of such families. Therefore, there is a strong need to patronize pulses cultivation and trade and promote their consumption to make India a hunger and malnutrition free nation.